PELATIHAN DASAR KEPEMIMPINAN UNTUK PENINGKATAN KREATIVITAS DAN PEMBENTUKAN KARAKTER MELALUI OUTBOUND BAGI SISWA MAN 2 INDRAMAYU - Agus Yudianto; Meddy Nurpratama; Sopyan Hadi; Umi Farida (Universitas YPPI Rembang, 2023)
This leadership training activity with the out bond model for students directly received high appreciation from the Head of Madrasah and Teachers and the Madrasah Council. Both in terms of the number of participants that exceeded the target participants and from the enthusiasm in participating in the entire leadership training event, the leadership training lead. With a training model like this, it will have a direct or indirect impact on the formation of morals, character and recreation for students. Continuous leadership training is the hope of many parties, especially regarding improving the quality of education and students' abilities, the material presented is very useful, especially practical things students can do when adapting to their environment. So that it is expected that students can get knowledge and skills obtained from leadership training as a forum for student activities that add skills and knowledge to the development of the growth process for students who are characterized and independent